Peningkatan Hasil Belajar Matematika Pada Materi Bilangan Bulat Menggunakan Metode Problem Solving Untuk Kelas IV SD Negeri Kedunglo - Alviani, Tri; Supriyono; Khaq, Muflikhul (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
This study aims to improve mathematics learning outcomes on integer material using problem solving methods for fourth graders at SD Negeri Kedunglo. This type of research is Classroom Action Research which consists of two cycles, each cycle meeting three times. Data analysis was carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that in the pre-cycle stage the average value of learning outcomes was 68.5 with a learning completeness percentage of 35%. In the first cycle the average value of learning outcomes was 82.5 with a percentage of learning completeness of 80% in the good category. In cycle II the average value of learning outcomes is 92 with the percentage of learning completeness reaching 100% in the very good category. Students' learning mastery has increased after learning using problem solving methods. Based on the results of the study, it can be concluded that the use of problem solving methods can improve the learning outcomes of fourth grade mathematics at SD Negeri Kedunglo on integer material.